Antepartum cerebral angiopathy presenting as middle cerebral artery aneurysm rupture – A rare case report from India - Abdul Jalal, Muhammed Jasim; E R, Sunesh; Kuruttukulam, Gigy Varkey; Chacko, Jacob; Manmadhan, Manju; Joshi, Manisha (Indian Journal of Case Reports, 2022)
The incidence of middle cerebral artery aneurysm rupture in pregnancy is rare. Rupture of an intracranial aneurysm is the most common cause of subarachnoid hemorrhage in pregnancy and during puerperium. Intracranial aneurysm rupture during pregnancy is disastrous for the mother as well as the fetus. We report a case of a dissecting left middle cerebral artery aneurysm in a 25-year-old woman, G2P1L1, at 18 weeks of gestation, who presented with a 1-day history of giddiness, slurring of speech, and facial deviation to the left.